Epidemiology, Diagnosis and Management of Paediatric Renal Diseases - Husnul Hayat, Rizwan Mahmood, Khurram Nawaz, Muhammad Usman Rafique, Beenish Babar, Aqsa Maryam Marith (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Paediatric renal diseases are an important cause of morbidity and mortality in children worldwide. Objectives: To evaluate the epidemiological profile, clinical presentations, diagnostic approaches, and management outcomes of renal diseases in paediatric patients presenting to a tertiary care centre. Study Design: Retrospective observational study. Place and Duration of Study: Department of Paediatrics, Avicenna Medical College & Hospital, Lahore from 1st April 2023 to 30th September 2023. Methodology: One hundred and seventy eight paediatric patients, aged from birth to 18 years diagnosed with renal diseases were included in the study. Data was collected included demographic details (age, sex, residence), clinical presentation (symptoms and signs), diagnostic evaluations (laboratory investigations, imaging studies, renal biopsy), and treatment modalities (medication, dialysis, or transplant where applicable). Results: There were 57.3% males and 42.7% females with a mean age of 8.6±4.2 years. The most common renal conditions were nephrotic syndrome (36.5%), congenital anomalies of the kidney and urinary tract (23.0%), and glomerulonephritis (14.6%). Key clinical presentations included proteinuria (62.9%), edema (52.8%), and hematuria (34.8%). Renal biopsies (n = 38) predominantly showed minimal change disease (50%) and focal segmental glomerulosclerosis (26.3%). Corticosteroids achieved remission in 72.3% of nephrotic syndrome cases, while 6.7% were steroid-resistant. Dialysis was required in 10.7% of patients, and 6 underwent renal transplantation. Conclusion: Nephrotic syndrome and congenital anomalies are the most prevalent renal conditions in children. Early diagnosis through routine screening and timely intervention remain critical to improving outcomes. Keywords: Epidemiology, Diagnosis, Management, Paediatric renal disease